Sulfur Heterocyclization and 1,3-Migration of Silicon in Reaction of 1,3-Diynes with Sodium Triisopropylsilanethiolate: One-Pot Synthesis of 2,5-Disubstituted 3-(Triisopropylsilyl)thiophenes - Tang, Jialiang; Ming, Ling; Zhao, Xiaoming (Synthesis, 2013)
Sulfur heterocyclization and 1,3-migration of silicon have been realized in the reactions of a range of 1,3-diynes with sodium triisopropylsilanethiolate in N,N-dimethylformamide. These provided 40–72% yields of 2,5-disubstituted 3-(triisopropylsilyl)thiophenes and up to 50% yield of 2,5-disubstituted thiophenes.
Keywords: 1,3-diynes; cyclizations; 1,3-migration of silicon; thiophene; sulfur heterocycles